The impact of accounting information systems on achieving harmonization between accounting treatments and market risks - Emad Harash essam; Jabbar D. Alsaidi; Eessam Hameed Dakil (Journal of Madenat Alelem University College, 2019)
This study attempts to clarify the relationship between the correct accounting treatments for financial events that occur as a result of the emergence of commercial transactions in accordance with the amendments made by the International Standard No. 39 in a group of listed companies in the Iraqi Stock Exchange (banking and financial investment companies) and market risks (interest rate risk, Currency risk, and other price risks) on the one hand. And the impact of accounting information systems used in these companies on the harmonization of accounting treatments and market risks. On the other hand through reading in the theoretical and applied literature that deals with this subject. As well as the views of a group